IMPACT OF WEIGHT TRAINING ON THE BODY COMPOSITION IN SEDENTARY MEN (Fiep Bulletin - online, 2014)
The present research had as objective to evaluate the effect of weight training on body composition indicators in sedentary men. Eight sedentary men (33,5 ± 3,7 years), but apparently healthy, were intentionally chosen for the research. The weight training happened during twelve weeks (two weekly sessions, in random days). Fourteen exercises composed the weight training program, each one made in three sets of 8 to 10 maximum repetition (RM). Measure skinfolds were collected before and after the intervention period. The results through Student test “t” compared revealed significant statistically difference p0,05). Longitudinal researches with a bigger number of samples and duration, using different weight training program should be done.
Keywords: Body Composition; Weight Training; Skinfolds